'You're on show all the time': Moderating emotional labour through space in the emergency department. (23rd June 2022) - Kirk, Kate; Cohen, Laurie; Edgley, Alison; Timmons, Stephen
Abstract: Aims: This is the second of two papers conceptualizing emotional labour in the emergency department (ED). This paper aims to understand the environmental 'moderators' of ED nurses' emotional labour. Design: Ethnography, through an interpretivist philosophy, enabled immersion in the ED setting, gathering the lived experiences and narratives of the ED nurses. Methods: Observation and semi‐structured interviews over a 6‐month period. Two hospital sites (one district general and one major trauma centre based in the United Kingdom. Results: Over 200 h of observation plus 18 formal/semi‐structured interviews were completed. Environmental, institutional and organizational dynamics of the emergency department instrumented the emotional labour undertaken by the nursing team. Time and space were found to be 'moderators' of ED nurses' emotional labour. This paper focusses on the relevance of space and in particular, 'excessive visibility' with little respite for the nurses from their intense emotional performance. Conclusion: Emotional labour is critical to staff well‐being and the way in which healthcare spaces are designed has an impact on emotional labour. Understanding how emotional labour is moderated in different clinical settings can inform organizational, environmental and workforce‐related decision‐making.